2004
DOI: 10.1523/jneurosci.3865-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

PSD93 Regulates Synaptic Stability at Neuronal Cholinergic Synapses

Abstract: Neuronal cholinergic synapses play important roles in both the PNS and CNS. However, the mechanisms that regulate the formation, maturation, and stability of neuronal cholinergic synapses are poorly understood. In this study, we use the readily accessible mouse superior cervical ganglion (SCG) and submandibular ganglion (SMG) to examine the assembly of the postsynaptic complex of neuronal cholinergic synapses. We find that novel splicing forms of PSD93 (postsynaptic density 93) are expressed in SCG. By immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 72 publications
2
102
0
5
Order By: Relevance
“…APC is also concentrated at neuronal glutamatergic synapses (Matsumine et al, 1996;Yanai et al, 2000) and is required, in vitro, for clustering of PSD-95 that, in turn, clusters AMPA receptors (Shimomura et al, 2007). Interestingly, the APC binding partners IQGAP1 and PSD-93/-95 are also shared between nicotinic and glutamatergic synapses (this study) (Conroy et al, 2003;Parker et al, 2004;Nuriya et al, 2005;Sheng and Hoogenraad, 2007). The emerging concept is that APC is a central organizer of a core postsynaptic complex that directs excitatory synapse assembly in the vertebrate nervous system.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…APC is also concentrated at neuronal glutamatergic synapses (Matsumine et al, 1996;Yanai et al, 2000) and is required, in vitro, for clustering of PSD-95 that, in turn, clusters AMPA receptors (Shimomura et al, 2007). Interestingly, the APC binding partners IQGAP1 and PSD-93/-95 are also shared between nicotinic and glutamatergic synapses (this study) (Conroy et al, 2003;Parker et al, 2004;Nuriya et al, 2005;Sheng and Hoogenraad, 2007). The emerging concept is that APC is a central organizer of a core postsynaptic complex that directs excitatory synapse assembly in the vertebrate nervous system.…”
Section: Discussionmentioning
confidence: 80%
“…Importantly, simultaneous block of APC's interactions with both EB1 and PSD-93 caused specific decreases in α3*nAChR clusters (Temburni et al, 2004). Postsynaptic accumulations of EB1 and PSD-93 were also reduced, although the latter is not essential for localizing α3*nAChRs at synapses (Conroy et al, 2003;Parker et al, 2004). …”
Section: Introductionmentioning
confidence: 97%
“…2B). Several of these mRNAs are known to be have roles in brain function, including Ntng1 (Nakashiba et al 2000), Dlgh2/ PSD93 (Tao et al 2003;Parker et al 2004), Nell2 (Matsuyama et al 2004), and Gabrg2 (Gunther et al 1995). Clearly, it will be interesting to follow up in future studies whether the ncRNAs identified here play any role in the biology of the mRNAs whose expression patterns they share.…”
Section: Tissue Profiling Of Putative Ncrnasmentioning
confidence: 85%
“…This latter feature enables ␣7-nAChRs to influence numerous calcium-dependent events, including gene expression Hu et al, 2002), as do NMDA receptors (Greenberg and Ziff, 2001;Vanhoutte and Bading, 2003). Also like NMDA receptors, ␣7-nAChRs and related subtypes codistribute with postsynaptic PDZ-containing proteins of the PSD-95/synapse-associated protein 90 family (Conroy et al, 2003;Parker et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A candidate mechanism for the initial decoupling might be calciumdriven changes in receptor phosphorylation, caused by calcium influx associated with ␣7-nAChR activation. Neuronal nicotinic receptors, including ␣7-nAChRs on somatic spines, are associated with postsynaptic scaffolds that mediate downstream signaling (Conroy et al, 2003;Parker et al, 2004;Temburni et al, 2004). How the scaffold components are affected by receptor activity is unknown.…”
mentioning
confidence: 99%